Effect of Effective Cough Education Video on Airway Clearance in Post General Anesthesia Patients - Rizki Ayu W; Burhan, Asmat; Kumala Dewi, Feti (Global Indonesia Health Care (GOICARE), 2024)
Background: Post-anesthesia disorders, particularly respiratory conditions related to hypoxia, can rapidly lead to fatal outcomes if not promptly identified and managed. Effective coughing techniques are essential for patients to expel phlegm efficiently. Purpose: This study aimed to evaluate the effectiveness of airway clearance in patient post-general anesthesia at RSI Purwokerto after viewing cough instruction videos. Methods: A quasi-experimental design, specifically the Pretest-Posttest Control Group Design, was employed. A total of 52 respondents were selected through purposive sampling. Data on airway clearance were collected using observation sheets. The Mann-Whitney U and Wilcoxon tests were utilized for data analysis. Results: Prior to viewing the instructional videos, the average airway clearance score was 1.03; this improved to 0.42 post-intervention. In the control group, the average score improved from 1.07 to 0.73 after education. The Wilcoxon test results indicated a significant difference in airway clearance before and after the intervention in both the experimental group (p = 0.001, p < 0.05) and the control group (p = 0.003, p < 0.05). Furthermore, the Mann-Whitney U test revealed a significant difference between the experimental and control groups post-intervention (p = 0.026, p < 0.05). Conclusion: The findings demonstrate that viewing cough instruction videos significantly improve airway clearance in patients who have undergone general anesthesia. This intervention is effective in enhancing respiratory outcomes in this patient population at RSI Purwokerto.